Pediatric Sports Specialization in Elite Ice Hockey Players. (January 2019) - Black, Sarah; Black, Kevin; Dhawan, Aman; Onks, Cayce; Seidenberg, Peter; Silvis, Matthew
Background: Pediatric sports specialization, defined as intense year-round training in a single sport as a result of excluding other sports for more than 8 months per year, is common in the United States. There are demonstrated physical and social risks to early pediatric sports specialization (defined as before age 12 years). While thought to be needed to acquire appropriate experience and excel in a given sport, there remains little information on when athletes at the highest levels of their sport specialized. This study aimed to define when professional and collegiate ice hockey players specialized. Hypothesis: Early sports specialization before age 12 years will not be common among elite-level (professional and collegiate) ice hockey players. Study Design: Retrospective cross-sectional survey study. Level of Evidence: Level 3. Methods: Male professional and collegiate ice hockey players within 1 National Hockey League organization and 2 National Collegiate Athletic Association (NCAA) organizations who were 18 years of age or older completed a survey at training camp detailing their history of sports participation and specialization. Results: A total of 91 athletes participated in the study (mean age, 22.8 years; range, 18-39 years). The mean age at the start of any sports participation was 4.5 years, and the mean age of sports specialization was 14.3 years. The mean age of specialization in the professional group, the NCAA Division I group, and the NCAA Division III group was 14.1, 14.5, and 14.6 years, respectively. Conclusion: Early pediatric sports specialization is not common in elite-level (professional and collegiate) ice hockey players. Clinical Relevance: Early pediatric sports specialization before age 12 years is not necessary for athletic success in professional and collegiate ice hockey. This study provides further evidence supporting the recommendations of the American Medical Society for Sports Medicine, American Academy of Pediatrics, and American Orthopaedic Society for Sports Medicine against early sports specialization.